Trainee Characteristics and Transfer of Training: Effect of Supervisory Support (A Study of Public Managers in Nepal) (Journal of Business and Management Research, 2017)
The significance of transfer of training to organizations has been recognized by researchers and managers alike, and the factors affecting the transfer have been the subject of many research studies in the West.  Considering the recent growth in training investment and coverage in public enterprises in Nepal without corresponding impact on their performance, the issue of transfer of training has gained importance in our context.  This study examines the effect of trainee characteristics, viz.: perceived content validity, learning transfer motivation, and self-efficacy on the level of training transfer and the role of supervisory support in this relationship in the context of Nepali public enterprises. Due to the non-availability of total population, the non-probability sampling method, specifically, quota sampling was used for selecting organizations, and then, managers meeting the pre-defined criteria, were selected for the study. Two hundred ninety-one officials from nine public enterprises participated in the survey.  The findings suggest that level of transfer of training is moderate, and two trainee characteristics, viz.: learning transfer motivation and content validity, positively and significantly affect transfer of training whereas self-efficacy does not have such effect. Supervisory support moderates the relationship between content validity and transfer of training but not between learning transfer motivation and transfer of training.  Managerial and research implications of the findings are discussed.